2000
DOI: 10.1007/s002400000142
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo stimulation of renal tubular p -aminohippurate transport by dexamethasone and triiodothyronine in human renal cell carcinoma

Abstract: This paper is the third of a long-term planned series of papers dealing with ex vivo investigations of drug transport in human kidney. The aims of this study are (a) to investigate whether or not human renal cell carcinoma (RCC) can actively accumulate p-aminohippurate (PAH) and (b) to test the response of RCC on dexamethasone or triiodothyronine (T3) using tissue slices ex vivo. By this approach, the accumulation capacity of RCC should be stimulated as a prerequisite for an increased uptake of anti-tumour dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Kidney slices from experimental animals have been widely used to characterize the renal uptake of organic anions through the basolateral membrane. Fleck et al (2000) demonstrated that human kidney slices retain organic anion transport activity. The present study focused on the use of human kidney slices to characterize the uptake of hOAT1 and hOAT3 substrates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kidney slices from experimental animals have been widely used to characterize the renal uptake of organic anions through the basolateral membrane. Fleck et al (2000) demonstrated that human kidney slices retain organic anion transport activity. The present study focused on the use of human kidney slices to characterize the uptake of hOAT1 and hOAT3 substrates.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies of the uptake of drugs by mammalian kidney slices have proved useful for examining uptake mechanisms. Fleck et al (2000Fleck et al ( , 2002 prepared kidney slices from human kidney and demonstrated the active accumulation of PAH and methotrexate, suggesting that human kidney slices also retain the activities of organic anion transporters. However, transport studies using human kidney tissue have not been thoroughly investigated focusing on the contribution of different transporters.…”
mentioning
confidence: 99%
“…Tubular transport of PAH is influenced by glucocorticoids (30), 1,25-dihydroxycholecalciferol (31), and sex steroids (29, 48 -50). PAH accumulation in human renal slices is increased by exposure to dexamethasone (114). Treatment of rats (particularly 5-to 10-day-old rats with immature kidney function) with the glucocorticoids prednisolone or dexamethasone results in increased renal excretion of PAH and increased PAH accumulation in renal cortical slices (30).…”
Section: A) Kinase-mediated Modulation Of Renal Basolateral Oamentioning
confidence: 99%
“…Human and rat kidney slices have been used as a tool to evaluate basolateral compound uptake into the kidney [172,173], drug-drug interactions [172,174] and nephrotoxicity [175]. Although these provide an effective tool, the uptake of compounds into kidney slices is lower than the in vivo renal intrinsic uptake clearance, which is partially due to diffusion from the surface of the kidney slice [18].…”
Section: Tissue Slicesmentioning
confidence: 99%